1998
DOI: 10.1083/jcb.143.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Calcium Current in Arteriolar Smooth Muscle by αvβ3 and α5β1 Integrin Ligands

Abstract: Vasoactive effects of soluble matrix proteins and integrin-binding peptides on arterioles are mediated by αvβ3 and α5β1 integrins. To examine the underlying mechanisms, we measured L-type Ca2+ channel current in arteriolar smooth muscle cells in response to integrin ligands. Whole-cell, inward Ba2+ currents were inhibited after application of soluble cyclic RGD peptide, vitronectin (VN), fibronectin (FN), either of two anti–β3 integrin antibodies, or monovalent β3 antibody. With VN or β3 antibody coated onto m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
171
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 53 publications
11
171
0
1
Order By: Relevance
“…First, AMPAR-mediated synaptic events may be permissive and simply provide the intermittent depolarization needed to allow integrin signaling influences on the otherwise voltage-blocked NMDARs and VSCCs to become manifest. Studies of nonneural cells have shown that integrins signal through FAK and Src kinases to phosphorylate and increase activities of plasma membrane calcium channels (Wu et al, 1998;Wu et al, 2001;Gui et al, 2006); we have shown similar integrin signaling effects on the NMDARs (Bernard-Trifilo et al, 2005). Second, direct integrin modulation of AMPA receptor function may be an important upstream event.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…First, AMPAR-mediated synaptic events may be permissive and simply provide the intermittent depolarization needed to allow integrin signaling influences on the otherwise voltage-blocked NMDARs and VSCCs to become manifest. Studies of nonneural cells have shown that integrins signal through FAK and Src kinases to phosphorylate and increase activities of plasma membrane calcium channels (Wu et al, 1998;Wu et al, 2001;Gui et al, 2006); we have shown similar integrin signaling effects on the NMDARs (Bernard-Trifilo et al, 2005). Second, direct integrin modulation of AMPA receptor function may be an important upstream event.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, when examined, influx is generally found to be mediated by VSCCs and dependent upon tyrosine kinase signaling (i.e., blocked by genistein) (Wu et al, 1998;Kwon et al, 2000;Wu et al, 2001). What distinguishes effects in neurons is the participation of neuron-specific receptors that produce depolarization (AMPA receptors) and voltage-dependent influx (e.g., NMDA receptors).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are the best characterized of the adhesion receptors for extracellular matrix components providing cells with the ability to adhere to surrounding connective tissue (FIGURE 3 (109,116,117,177,178). It has also been observed that the expression of these two integrins is increased in mesenteric arteries from spontaneously hypertensive rats (88), possibly accounting for the increased vascular myogenic tone reported in these animals (58, 59, 149).…”
Section: Integrin Receptors: Dynamic Sites Of Adhesion To the Extracementioning
confidence: 90%
“…Integrins are the primary transducers of mechanical force to the cell's cytoskeleton (36,37), and integrin stimulation is involved in a wide range of cellular signaling, including altering calcium dynamics (11,12) and phenotypic behavior (38)(39)(40) in VSMCs. The mechanical loading of the blast and the resulting hypercontractility both likely result in abnormal integrin stimulation, potentially mediating the observed vasospasm behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of vascular smooth muscle have revealed that direct stimulation of integrins induces enhanced calcium activity (11,12) and myosin light chain phosphorylation (13). Cyclic mechanical stimulation within physiological ranges induces populations of vascular smooth muscle cells (VSMCs) to shift toward a contractile phenotype (14), while mechanical stresses of a higher magnitude, mimicking chronic hypertension, induce smooth muscle proliferation and extracellular matrix (ECM) remodeling (15).…”
mentioning
confidence: 99%